Culturing Undaria pinnatifida Gametophytes - Mandrekar, Pushkar (Auckland University of Technology, 2018)
Undaria pinnatifida is a species of brown laminarian seaweed, primarily found in its native habitat, in the temperate waters of East Asia. The seaweed was accidentally introduced to New Zealand in the late 1980’s and since then has spread as a pest, uncontrollably around the country’s extensive coastline. It is farmed extensively in Japan, China and S. Korea, and because of its global commercial importance, there is an interest in farming U. pinnatifida in NZ waters. This study showcases the viability of growing and maintaining vegetative gametophytes in a controlled laboratory environment to be possibly used as a seeding stock for any future seaweed aquaculture in NZ. The gametophytes were successfully cultured in “French” seaweed media under 24 hr. LD irradiance cycle at 40 µmol.m-2s-1 (~2000 lux) and a constant temperature of 22°C in an environmental chamber. The research was further expanded upon to trial gametophyte growth in aquaculture effluent. Aquaculture effluent from a paua farm was also successfully used to grow and maintain vegetative gametophytes, which also displayed total ammonia uptake during the process. Crude fucoidan, a sulphated polysaccharide was extracted at 10% w/w from the freeze-dried vegetative gametophytes using a deionized water extraction method.
Keywords: Undaria; Seaweed; Aquaculture; Farming; Integrated aquaculture; Fucoidan